THE LEVEL OF ADHERENCE TO CONTROL PATIENTS FOR FIXED ORTHODONTIC AMONG THE FACULTY OF DENTISTRY STUDENTS AT THE PRIMA UNIVERSITY OF INDONESIA DURING THE PANDEMIC - Mutaqqin, Zulfan; Arts, Tricya Merrina; Hadi, Lina (Universitas Halu Oleo, 2021)
AbstractBackground: Currently, the interest and awareness to maintain oral health is increasing, it is no longer limited to fillings and extractions, one of which is orthodontic treatment. The increasing interest in orthodontic treatment is due to the high prevalence rate of malocclusions consisting of mild to severe malocclusions. Patient non-compliance with scheduled visits is an indication of the failure of orthodontic treatment. Repeated failures will reduce the quality of care. Malocclusion is an abnormal dentofacial condition with or without impaired craniofacial connection. Malocclusion can affect facial aesthetic appearance, mouth function, and psychosocial. Malocclusion is the most common dental problem with a high prevalence ranging from 20% to 100% reported in various studies. Multifactorial causes of malocclusion, namely heredity, environmental factors or a combination of the two in individuals with malocclusion. Purpose: This study aimed to determine the level of adherence to control of fixed orthodontic patients based on the characteristics of students at the Faculty of Dentistry at the Prime University of Indonesia during the pandemic. Method: This research is non-experimental research with an observational descriptive method. The study was conducted on students of the Faculty of Dentistry, Universitas Prima Indonesia with a total sample of 30 people. Results: Based on the results of the research, it was concluded that the level of adherence to fixed orthodontic control of students during the Covid-19 pandemic was low and there was no relationship between characteristics and the level of patient compliance during the pandemic.Â Keywords: Malocclusion, Orthodontics, Dentofacial, Covid-19.